Amoxicillin for clinically unsuspected pneumonia in primary care: subgroup analysis. Issue 1 (5th November 2015) - Teepe, Jolien; Little, Paul; Elshof, Nori; Broekhuizen, Berna D.L.; Moore, Michael; Stuart, Beth; Butler, Chris C.; Hood, Kerenza; Ieven, Margareta; Coenen, Samuel; Goossens, Herman; Verheij, Theo J.M.
Clinically unsuspected pneumonia does benefit from antibiotic treatment in terms of duration and severity of symptoms http://ow.ly/T46up Antibiotic treatment is recommended for pneumonia [1, 2]. However, some studies have suggested that the milder spectrum of pneumonia in primary care does not have important adverse consequences if missed and, therefore, managed without antibiotics [3–5]. Better insight in the effects of antibiotics for pneumonia in primary care could improve patient information and management.